Pediatric giant cell glioblastoma: a rare entity - Vijayan, Poornima; Shemin, Zuhara; Saleem, Sharmina; Ponniah, Anupama (International Journal of Contemporary Pediatrics, 2017)
Giant cell glioblastoma (GCG) is a rare subtype of glioblastoma multiforme (GBM) which represents 0.8% of all brain tumors and 5% of glioblastomas. This entity is all the more rarer in the pediatric age group. And, due to the limited number of case reports and case series in literature, its epidemiology, natural history and follow up are not well documented. We present this case for its rarity. A 14-year-old girl presented with history of recent onset headache and vomiting from last 10 days. Magnetic resonance imaging (MRI) brain revealed a mass lesion in the right temporo-parietal region, suggestive of a high-grade glioma. Histopathological examination revealed features typical of giant cell glioblastoma. Giant cell glioblastoma, is an extremely rare variant of gliobastoma multiforme, merits special mention because it has been hypothesized to be associated with a longer survival compared with GBM in both adults and children, possibly because of the younger age at presentation, certain histopathological and molecular characteristics of this entity.